1999
DOI: 10.5271/sjweh.381
|View full text |Cite
|
Sign up to set email alerts
|

Increase in interleukin-6 and fibrinogen in peripheral blood after swine dust inhalation

Abstract: Objectives The inhalation of dust from swine confinement buildings causes inflammatoly responses in the airways with a rise of interleukin-6 (IL-6). The purpose of this study was to confirm the increase in serum IL-6 after inhalation of swine dust and investigate a possible increase in plasma fibrinogen. Methods Eight healthy nonsmoking volunteers inhaled dust for 4 hours inside a swine confinement building. Inhalable dust and endotoxin were sampled. The collcentrations of IL-6 and fibrinogen were determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Inhalation of dust containing endotoxin from a swine confinement building caused an inflammatory response in volunteers with an increase of fibrinogen by around 1 g/L [Sjögren et al, 1999]. However, inflammatory markers increased much less after exposure in swine farmers compared with the increase among previously non-exposed volunteers [Palmberg et al, 2002].…”
Section: Re: Occupational Endotoxin-exposure and Possible Health Effementioning
confidence: 96%
“…Inhalation of dust containing endotoxin from a swine confinement building caused an inflammatory response in volunteers with an increase of fibrinogen by around 1 g/L [Sjögren et al, 1999]. However, inflammatory markers increased much less after exposure in swine farmers compared with the increase among previously non-exposed volunteers [Palmberg et al, 2002].…”
Section: Re: Occupational Endotoxin-exposure and Possible Health Effementioning
confidence: 96%
“…Indeed, the association between high Lp(a) serum levels and high plasma concentrations of the proinflammatory cytokine interleukin-6 (IL-6) suggested that genetic control of Lp(a) levels may be modulated by age and environmental factors, such as the chronic subclinical inflammatory process (25). Similarly, the concentrations of IL-6 and fibrinogen correlated (26)(27)(28). Thus, markers of cardiovascular risk are also acute-phase reactants (29).…”
Section: Ferricyanide Reduction In Diabetic Nephropathymentioning
confidence: 99%
“…rhusiopathiae. Disease associated with the pathogen E. rhusiopathiae has been recognized in swine occupations since the (97,104) Fibrinogen (106) 19th century (141)(142)(143). There are three human disease syndromes associated with this pathogen: a cutaneous form (erysipeloid), an acute or septicemic form, and a chronic form (141,143,144).…”
Section: Identified Hazards Of Swine Cafos Air-associated Contaminantsmentioning
confidence: 99%